Perineal Massage with VCO Reduces Perineal Rupture in Labor: Pijat Perineum dengan VCO Mengurangi Risiko Robekan Perineum Saat Persalinan - Nela Akhmalia; Rafhani Rosyidah; Hesty Widowati; Yanik Purwanti (Academia Open, 2025)
ABSTRACTGeneral Background: Maternal mortality is associated with obstetric complications, including postpartum hemorrhage caused by birth canal trauma. Specific Background: Perineal rupture occurs in approximately 75% of vaginal deliveries in Indonesia and is associated with parity, maternal age, fetal weight, and perineal elasticity. Perineal massage using virgin coconut oil (VCO) is considered a nonpharmacological approach to maintain tissue flexibility. Knowledge Gap: Empirical evidence examining VCO-based perineal massage for preventing perineal rupture remains limited. Aims: This study evaluated perineal massage with VCO for preventing perineal rupture among pregnant women. Results: A quasi-experimental post-test only non-equivalent control group design involving 56 pregnant women at 34–38 weeks of gestation was conducted. The intervention group received weekly 10-minute massage. The intervention group showed 64.3% without rupture, while 70.4% of the control group experienced rupture, with a significant association (p = 0.021; OR = 0.234). Novelty: This study provides clinical evidence supporting VCO-based perineal massage as an antenatal preventive method. Implications: Integration of this technique into antenatal care may support safer vaginal delivery and reduce birth canal trauma. Highlights: Weekly Intervention Beginning at 34 Weeks Shows Lower Incidence of Birth Canal Tearing. Participants Receiving the Procedure Demonstrated Higher Rates of Intact Tissue During Delivery. Statistical Testing Identified a Significant Association Between Antenatal Manual Therapy and Tissue Integrity Outcomes. Keywords: Perineal Rupture, Virgin Coconut Oil, Antenatal Care, Birth Canal Trauma, Maternal Delivery Outcomes